Drug resistance and ATP-dependent conjugate transport mediated by the apical multidrug resistance protein, MRP2, permanently expressed in human and canine cells - Cui, Yunhai; König, Jörg; Spring, Herbert; Keppler, Dietrich (Molecular pharmacology, 1999)
The multidrug resistance protein MRP1 functions as an ATP-dependent conjugate export pump and confers multidrug resistance. We cloned MRP2 (symbol ABCC2), a MRP family member localized to the apical membrane of polarized cells. Stable expression of MRP2 in transfected human embryonic kidney (HEK-293) and Madin-Darby canine kidney (MDCK) cells was enhanced by inhibitors of histone deacetylase. In polarized MDCK cells, both rat and human MRP2 were sorted to the apical plasma membrane. An antibody raised against the amino terminus of rat MRP2 recognized the recombinant protein on the apical surface of nonpermeabilized cells, providing direct evidence for the extracellular localization of the amino terminus of MRP2. ATP-dependent transport by recombinant human and rat MRP2 was measured with membrane vesicles from stably transfected cells. The Km value of human MRP2 was 1.0 ± 0.1 μM for leukotriene C4 and 7.2 ± 0.7 μM for 17β-glucuronosyl estradiol; theKm values of human MRP1 were 0.1 ± 0.02 μM for leukotriene C4 and 1.5 ± 0.3 μM for 17β-glucoronosyl estradiol. Thus, the conjugate-transporting ATPases MRP2 and MRP1 differ not only by their domain-specific localization but also by their kinetic properties. Drug resistance conferred by recombinant MRP2 was studied in MDCK and HEK-293 cells using cell viability assays. Expression of human and rat MRP2 enhanced the resistance of MDCK cells to etoposide 5.0-fold and 3.8-fold and to vincristine 2.3- and 6.0-fold, respectively. Buthionine sulfoximine reduced resistance to these drugs. Human MRP2 overexpressed in HEK-293 cells enhanced the resistance to etoposide (4-fold), cisplatin (10-fold), doxorubicin (7.8-fold), and epirubicin (5-fold). These results demonstrate that MRP2 confers resistance to cytotoxic drugs.
Gesehen am 23.02.2021